The United Nations Environment Programme (UNEP) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
The United Nations Environment Programme (UNEP) In the 1960s and early 1970s anxiety over industrial pollution led to the Stockholm Conference on the Human Environment in 1972 which, in turn, resulted in the establishment of the United Nations...